Rainwater as an Alternative to Urban Clean Water Comparison between Bangladesh and Indonesia - Mustafa, Annisa Fitri; Koestoer, Raldi Hendro; Hartono, Djoko Mulyo; Hasibuan, Hayati Sari (Empiricism Journal, 2026)
Urban water security is increasingly challenged by rapid urbanization, groundwater depletion, climate change, and rising water demand. Rainwater Harvesting (RWH) has been recognized as a sustainable approach to diversify water sources and enhance urban water resilience, particularly in tropical countries with high rainfall potential. However, previous studies have primarily focused on the technical feasibility, water-saving performance, and water-quality aspects of RWH, while limited attention has been given to comparative analyses of policy frameworks, institutional arrangements, and implementation mechanisms. This study aims to compare RWH policies and governance in Bangladesh and Indonesia and to formulate policy recommendations for strengthening RWH implementation in Indonesia. This study employed a comparative policy review based on a systematic literature review and policy-document analysis. Relevant scientific publications and policy documents published between 2010 and 2024 were collected from Scopus, Google Scholar, and Mendeley Search. The selected documents were analyzed using four comparative dimensions: technical implementation, funding mechanisms, regulatory–institutional frameworks, and scope of technology application. The findings indicate that Bangladesh has integrated RWH into national development plans, water-supply strategies, and institutional programs supported by government agencies, financial incentives, and multi-stakeholder collaboration. In contrast, Indonesia already possesses regulations related to water resources and rainwater management, but RWH implementation remains fragmented due to limited institutional coordination, insufficient funding mechanisms, and the absence of an integrated national implementation framework. The study concludes that effective RWH implementation depends not only on rainfall availability but also on governance capacity, regulatory support, financing mechanisms, and institutional coordination. The novelty of this study lies in synthesizing RWH governance experiences in Bangladesh and Indonesia to generate policy recommendations for improving urban water security in Indonesia.